IDENTIFICATION OF OCEANOGRAPHIC PARAMETERS FOR DETERMINING PELAGIC TUNA FISHING GROUND IN THE NORTH PAPUA WATERS USING MULTI-SENSOR SATELLITE DATA - VlNCENTIUS SlREGAR; HAROLD JOPPIE DAVIDO WAAS (SEAMEO BIOTROP, 2006)
The North Papua waters as one of the important fishing grounds in the world contribute approximately 75% of world production of pelagic tunas. These fishing grounds are still determined by hunting method. This method is time consuming and costly. However, in many areas determination of fishing ground using satellited data lias been applied by detecting the important oceanographic parameter of the presence of fish schooling such as, sea surface temperature and chlorophyl. Mostly these parameters are used integratedly. The aim of this study is to assess the important oceanographic parameters detected from multi-sensor satellites (NOAA/AVHRR, Seawifs and Topex Poisedon) for determining fishing ground of pelagic tunas in the North Papua waters at east season. The parameters include Sea Surface Temperature (STT), chlorophyl-a and currents. The availability of data from optic sensor (Seawifs: chl-a and AVHRR: Thermal) is limited by the presence of cloud cover. In that case, Topex Poseidon satellite data can be used to provide the currents data. The integration of data from multi-sensors increases the availability of the oceanographic parameters for prediction of the potential fishing zones in the study area. Key words :Â Â Identification, oceanographic parameter, sea surface-temperature, chlorophyl-a, multi sensors, pelagic tuna, North Papua-waters